Q: What would 2a x 2 be?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

The answer is 4a^2.

2a2

The height of an equilateral triangle is √3/2 x side_length. So for an equilateral triangle of side length 2a, the area is: area = 1/2 x base x height 1/2 x (2a) x (√3/2 x 2a) = √3 a2

144a2b

The quadratic formula originated from the concept of completing the square. let's take ax2 + bx + c = 0. To complete the square, solve for x. Subtract c. ax2 + bx = -c. Then divide by a [notice- if there is no a value, then a=1]. x2 + bx/a = -c/a. Add (b/2a)2 to both sides. x2 + bx/a + b2/4a2 = -c/a + b2/4a2 Factor/Reformat. (x + b/2a)2 = (b2-4ac) / 4a2 (x + b/2a)2 = [(b2-4ac) / 2a]2 Square-root both sides. x + b/2a = ± √(b2-4ac) / 2a Subtract b/2a. x = -b/2a ± √(b2-4ac) / 2a Combine terms. x = [-b ± √(b2-4ac)] / 2a

Related questions

The answer is 4a^2.

2a2

The height of an equilateral triangle is √3/2 x side_length. So for an equilateral triangle of side length 2a, the area is: area = 1/2 x base x height 1/2 x (2a) x (√3/2 x 2a) = √3 a2

Factor them. 2 x 2 x a = 4a 2 x 5 x a x a = 10a2 Select the common factors. 2 x a = 2a, the GCF.

4a

144a2b

2a - a = a

a x a means that a is multiplied by a. 2a means that a is multiplied by 2. Unless a happens to be 2, a x a will give a different result.The difference is a x (a-2). for example if a = 2, then the difference is zero. If a = 3, the difference is 3The operators are different: 2a = a + a (addition).

4aa-bb fits the special type of polynomial in the form of x**2-y**2 which can be rewritten as (x-y)(x+y) sqrt(4aa) = 2a sqrt(bb) = b (2a-b)(2a+b)

The quadratic formula originated from the concept of completing the square. let's take ax2 + bx + c = 0. To complete the square, solve for x. Subtract c. ax2 + bx = -c. Then divide by a [notice- if there is no a value, then a=1]. x2 + bx/a = -c/a. Add (b/2a)2 to both sides. x2 + bx/a + b2/4a2 = -c/a + b2/4a2 Factor/Reformat. (x + b/2a)2 = (b2-4ac) / 4a2 (x + b/2a)2 = [(b2-4ac) / 2a]2 Square-root both sides. x + b/2a = ± √(b2-4ac) / 2a Subtract b/2a. x = -b/2a ± √(b2-4ac) / 2a Combine terms. x = [-b ± √(b2-4ac)] / 2a

The quadratic formula originated from the concept of completing the square. let's take ax2 + bx + c = 0. To complete the square, solve for x. Subtract c. ax2 + bx = -c. Then divide by a [notice- if there is no a value, then a=1]. x2 + bx/a = -c/a. Add (b/2a)2 to both sides. x2 + bx/a + b2/4a2 = -c/a + b2/4a2 Factor/Reformat. (x + b/2a)2 = (b2-4ac) / 4a2 (x + b/2a)2 = [(b2-4ac) / 2a]2 Square-root both sides. x + b/2a = ± √(b2-4ac) / 2a Subtract b/2a. x = -b/2a ± √(b2-4ac) / 2a Combine terms. x = [-b ± √(b2-4ac)] / 2a

2x^2 - 21x + c = 0 x^2 - 21x/2 + c/2 = 0 (x + a)(x + 2a)= x^2 - 21x/2 + c/2 x^2 + 3a + 2a^2 3a = -21/2 ------> a = -7/2 2a^2 = c/2 ---> 49/2 = c/2 ---> c = 49